The Estimation of Multi-dimensional Fixed Effects Panel Data Models - Laszlo Balazsi; Laszlo Matyas; Tom J. Wansbeek (Center for Economic Studies and ifo Institute (CESifo), 2015)
The paper introduces the appropriate within estimators for the most frequently used three-dimensional fixed effects panel data models. It analyzes the behavior of these estimators in the cases of no self-flow data, unbalanced data, and dynamic autoregressive models. The main results are then generalized for higher dimensional panel data sets as well.
Keywords: C10; C20; C40; F17; F47; 330; panel data; unbalanced panel; dynamic panel data model; multidimensional panel data; fixed effects; trade models; gravity models; FDI